Investigation into shrinkage of stretchable denim fabric and its consumption in marker making by varying drying temperatures - Muhammad Amir; Shenela Naqvi; Farhana Naeem (Mehran University Research Journal of Engineering and Technology, 2023)
This investigation was carried out to minimize Cotton and Cotton–polyester stretchable denim fabrics consumption for garment development through marker making. It was achieved by controlling fabric shrinkage by reducing drying temperature after washing in fixed processing time, without compromising properties of denim; Tensile strength, Stretch (growth and recovery at constant and cyclic loading) and colour strength (K/S) of required shade. warp faced 3x1 and 2x1 denim containing elastin were constructed and then washed using same recipe as per industrial practice however drying temperatures were set at 50oC, 60oC and 70oC, separately. After measuring shrinkage and evaluating tensile strength, Stretch, Growth and recovery at constant and cyclic loading and colour strength (K/S) using standard test methods; trouser marker layout was developed by employing Gerber technology to investigate fabrics consumption. The obtained shrinkage % demonstrated a significant coefficient of determination (R2=0.9931) against drying temperatures. Relation of tensile strength, colour strength and growth were insignificant however stretch, growth and recovery at static and cyclic loading were significantly affected by changing temperatures. Average shrinkage % of stretchable denim fabric was 1.71% in warp and 8.24% in weft at 50oC. It increased to 12.05% in weft at 60oC however remained same in warp while against 70oC it was 1.82% in warp and 14.08% in weft. 10 minutes drying time was kept same for selected drying temperatures. It was found that fabric consumption reduced to 1.25 m per trouser from 1.32 m per trouser by setting drying temperature at 50oC. Present research work provides guideline to denim industries to process stretchable denim at lower drying temperature i.e., 50oC because it not only reduced consumption of elastin containing denim fabric, but it also makes process cost effective as well as environmentally friendly.